Contacts with large, active individuals intensify the predation risk of small conspecifics. Issue 11 (3rd November 2016) - Yamaguchi, Aya; Takatsu, Kunio; Kishida, Osamu
Abstract: Size variation within a population can influence the structure of ecosystem interactions, because ecological performance differs between individuals of different sizes. Although the impact of size variation in a predator species on the structure of interactions is well understood, our knowledge about how size variation in a prey species might modify the interactions between predators and prey is very limited. Here, by examining the interactions between predatory Hynobius retardatus salamander larvae and their prey, Rana pirica frog tadpoles, we investigated how large prey individuals affect the predation mortality of small prey conspecifics. First, in an experiment conducted in a field pond in which we manipulated the presence of salamanders and large tadpoles (i.e., large enough to protect them against salamander predation) with small tadpoles, we showed that in the presence of large tadpoles the mortality of small tadpoles from salamander predation was increased. On the basis of our observations of the activity of individuals, we hypothesized that active large tadpoles caused physical disturbances, which in turn caused the small tadpoles to move, and thus increased their encounter frequency with the predatory salamanders. To test this hypothesis, we conducted a laboratory experiment in small tanks with three players (i.e., one salamander as predator, one small tadpole as focal prey, and either a small or a large tadpole as the prospective movement inducer). In each tank, we manipulated the presence or absence of a movement inducer, and, when present, its size (large or small) and access (caged or uncaged) to the focal prey. In the presence of a large, uncaged movement inducer, the focal prey was more active and suffered from higher predation mortality compared with the other treatments, because the large movement inducer (unlike a small movement inducer) moved actively and, when uncaged, could stimulate movement of the focal prey through direct contact. The results indicated that high activity of large prey individuals and the resulting behavioral interactions with small conspecifics via direct contact indirectly increased the mortality of the small prey.